2015
DOI: 10.2298/ciceq140418027g
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cadmium (II) from aqueous solution using fermented grape marc as a new adsorbent

Abstract: Biosorption of cadmium from aqueous solutions using fermented grape marc is investigated in this paper as well as influence of the most important factors, such as: contact time, granulation of biosorbent and the initial concentration of metal ions, is investigated in this paper. The equilibrium sorption of cadmium ions is achieved after 15-20 min., depending on the initial concentration of metal ions. Such a short time needed to achieve the equilibrium indicates that mass sorption is dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Batch adsorption experiments were performed for both biosorbents GM-HCl and GM-CA by shaking the dispersion prepared by mixing 3 mg of the dry biosorbent with 3 ml of HgCl2 aqueous solution at known concentrations in the range of 23-300 mg L -1 [18,22]. The mixture was shaken for 20 h at room temperature and 250 rpm and filtrated through a 0.20 µm filter to remove the sorbent.…”
Section: Hg(ii) Adsorption Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Batch adsorption experiments were performed for both biosorbents GM-HCl and GM-CA by shaking the dispersion prepared by mixing 3 mg of the dry biosorbent with 3 ml of HgCl2 aqueous solution at known concentrations in the range of 23-300 mg L -1 [18,22]. The mixture was shaken for 20 h at room temperature and 250 rpm and filtrated through a 0.20 µm filter to remove the sorbent.…”
Section: Hg(ii) Adsorption Experimentsmentioning
confidence: 99%
“…The adsorption data were fitted into four linearized Langmuir, Freundlich, Temkin, and D-R isotherms [22]. Langmuir isotherm model describes the formation of a monolayer adsorbate on the outer surface of the biosorbent, and it is represented in the following linear form [12,18,22,23,24]:…”
Section: Isotherms Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results [11] showed that grape marc is a cellulosic material of multilayered structure whose layers are interconnected by a system of channels and pores, which form a relatively large specific surface area. The presence of pores is suitable for diffusion of metal ions and their adsorption on numerous internal active centers.…”
Section: Introductionmentioning
confidence: 99%